Statistical Trends of School Size, Location and Enrolment: An Evaluation of Public Junior Secondary Schools for Sustainable Development (World Journal of Vocational Education and Training, 2020)
This is a trend study of School Size, Location and Enrolment Figures of Junior secondary schools in Akwa Ibom State of Nigeria covering 2008 – 2016 with implications on sustainable development. The study was tailored to follow the ex-post facto research design. This study was a census, hence the entire population of 227 public secondary schools were used. Secondary quantitative data were obtained using “School Size, Location and Enrolment Figures Checklist (SSLEFC)” were analysed using descriptive statistics, while line graphs and bar charts were used to illustrate the statistical trends. The hypotheses were tested using the independent t-test statistical approach. Findings showed that higher rates of enrolment were recorded in large and urban schools than in small schools and rural schools respectively. The mean differences in the enrolment trend among urban and provincial schools were factually huge. It was presumed that there is an upward pattern in enrolment in all the schools from 2008 – 2013 and a descending pattern from 2015– 2016. Based on this conclusion, implications were discussed, while it was recommended, among others, that infrastructural provisions and adequate supply of qualified personnel be allocated to urban and rural schools evenly, to discourage rural-urban migration but promote active rural participation in Education, as well as foster sustainability in schools.